Josiah's reform and the dynamics of defilement: Israelite rites of violence and the making of a biblical text - Monroe, Lauren A. S. (Oxford University Press, 2011)
Chapters 22 and 23 of 2 Kings tell the story of the religious reforms of the Judean King Josiah, who systematically destroyed the cult places and installations where his own people worshipped in order to purify Israelite religion and consolidate religious authority in the hands of the Jerusalem temple priests. This is a study of the text